THE INTERNATIONALIZATION OF HIGHER EDUCATION: AN EMERGING POLITICAL AGENDA - Malcolm McVicar (Сравнительная политика, 2015)
Given growing importance of education as a factor of internal development and in the context of globalization universities can be considered to be international economic actors playing an increasingly significant role in economic and political agenda. Universities face a lot of challenges, to wit: quality control, further privatization of higher education and for-profit education, the problem of innovations and advanced technologies, the emergence of international labour market etc. Therefore internationalization of higher education determines the necessity to reform and adapt universities around the globe.